Swimming performance changes during the final 3 weeks of training leading to the sydney 2000 olympic games - Mujika, I.; Padilla, S.; Pyne, D. (International Journal of Sports Medicine, 2002)
The purpose of this study was to determine the magnitude of the swimming performance change during the final 3 weeks of training (F3T) leading to the Sydney 2000 Olympic Games. Olympic swimmers who took part in the same event or events at the Telstra 2000 Grand Prix Series in Melbourne, Australia, (26 - 27 August 2000), and 21 - 28 d later at the Sydney 2000 Olympic Games (16 - 23 September 2000) were included in this analysis. A total of 99 performances (50 male, 49 female) were analysed. The overall performance improvement between pre- and post-F3T conditions for all swimmers was 2.18 +/- 1.50 % (p < 0.0001), (range - 1.14 % to 6.02 %). A total of 91 of the 99 analysed performances were faster after the F3T and only 8 were slower. The percentage improvement with F3T was significantly higher (P < 0.01) in males (2.57 +/- 1.45 %) than in females (1.78 +/- 1.45 %). In conclusion, the pre-Olympic F3T elicited a significant performance improvement of 2.57 % for male and 1.78 % for female swimmers at the Sydney 2000 Olympic Games. The magnitude was similar for all competition events, and was achieved by swimmers from different countries and performance levels. These data provide a quantitative framework for coaches and swimmers to set realistic performance goals based on individual performance levels before the final training phase leading to important competitions.